How fast can we see? The latency development in human infants to pattern, orientation, and direction-reversal visual evoked potentials - Lee, J (2013)
The goal of this thesis is to track latency changes in three visual evoked potentials (VEP) stimuli as an indication of overall brain development, in order to provide a normative baseline to differentiate visual and neurological development from pathological processes. VEP- neural electrical activity recorded from the scalp surface and synchronized with visual stimulus transitions- is one of the common techniques in understanding infant vision development. Past work has concentrated on responses to pattern reversal and to the latency of the initial positive peak. Here we compare the timing of responses to pattern, orientation, and direction-reversal VEPs, and transient peak latencies to those calculated from the gradient of steady-state phase against reversal rate. The three stimuli were tested in 81 adults at 1- 16 r/s and 137 infants (3.6- 79.0 weeks) at 2- 8 r/s. Initial responses to orientation and direction were as fast as for contrast- around 100 ms, consistent with other findings that V1 is orientation selective. Cortical processing for both OR and DR yielded longer latencies (200 ms) by the calculated method, perhaps reflecting more involvement of higher visual processing in comparison to PR. Orientation and direction latencies also had a delayed onset and longer developmental period to reach maturity. Infants reached adult transient PR latency values by 15 weeks, for OR by 50 weeks, and for DR by 10 weeks. For the calculated latency, infants reached both adult PR and DR latencies by 30 weeks while OR showed little change across age. We successfully confirmed that (1) phase-based calculation of latency is effective, easy to use, and taps into a different cortical pathway; (2) motion processing has an additional, faster, subcortical pathway; (3) a parallel processing of initial contrast and orientation; and (4) later visual processing is not only developmentally delayed for all three stimuli but also more vulnerable to perinatal brain damage. These latency differences provided a baseline for clinical evaluations where identification of delayed latencies should aid early diagnosis and guide therapies for adults and infants.